Pengaruh Kompetensi SDM, Penerapan Standar Akuntansi Dan Sistem Akuntansi Keuangan Terhadap Kualitas Laporan Keuangan Pada Koperasi Langgeng Jaya Abadi di Pati. - Heru Pranoto, Sarastanto Aulia; Sopi, Sopi; Triasningrum, Frida Widyawati (Sekolah Tinggi Ilmu Ekonomi Semarang, 2025)
This study aims to determine the effect of human resource competence, the application of accounting standards, and the financial accounting system on the quality of financial statements at Koperasi Langgeng Jaya Abadi in Pati. The quality of financial statements is the final result of the accounting process that provides understandable financial information for users and can be used for future decision-making. The population in this study consisted of 32 respondents, including educators and education personnel who manage finances within Koperasi Langgeng Jaya Abadi Pati. The independent variables in this study are human resource competence (X1), application of accounting standards (X2), and financial accounting system (X3). The dependent variable is the quality of financial statements (Y). Data were collected using a questionnaire, and the analysis technique used was multiple regression. The results showed that the human resource competence variable had a regression coefficient value of 0.229 with a significance value of 0.012, indicating that human resource competence has a positive and significant effect on the quality of financial statements. The accounting standards application variable showed a regression coefficient of 1.035 with a significance value of 0.000, proving that the application of accounting standards has a positive and significant effect on the quality of financial statements. The financial accounting system variable showed a regression coefficient of 0.220 with a significance value of 0.020, indicating that the financial accounting system has a positive and significant effect on the quality of financial statements. It is recommended that Koperasi Langgeng Jaya Abadi Pati improve the competence of financial management employees in managing and presenting financial statements. This is because some employees still have low skills and knowledge in accounting. The cooperative should also evaluate the application of accounting standards to ensure that financial reports comply with the applicable accounting rules and present financial information fairly and fairly, as this is an obligation.